SEJARAH PEMIKIRAN EKONOMI ISLAM AL SYAIBANI DAN ABU UBAID - Salidin Wally (TAHKIM, 2018)
This article describes about the Islamic economic thinking according to Islamic economist Al Syaibani and Abu Ubaid. In his discussion raised the thinking of two prominent Islamic economist Al Syaibani who emphasized his thoughts on microeconomics and embodied in his work namely Al-Kasb, and also Abu Ubaid's ideas which emphasize his thoughts on macroeconomics by exploring in detail in his book that is Al-Amwal discusses state rights and obligations. And concluded that the thoughts of these two figures differed in view in response to economic problems, but both have a common goal that is for the welfare of the ummah and the main goal of the keridhoan Allah.